Commentary: UNDER THE NAME OF EDSPEAK: SANDERS REVISITED - Brown, Stephen I. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1995)
ABSTRACT. James T. Sanders recently published an article in this journal (Vol. 29 No. 1) in which he identified what he believed to be a "particularly empty form of educational discourse" - cleverly dubbed "Edspeak." This essay points out that in his description of the formula for that form of discourse, Sanders has become a victim of his own criticism, thus vitiating the criticism itself. RÉSUMÉ. James T. Sanders a récemment publié ici (vol. 29, no. 1) un article où il disait avoir identifié ce qu’il croyait être "une sorte de discourse particulièrement vide" - qu’il a astucieusement appelé "Edspeak". Le présent article montre que, dans sa description de la formule que revêt cette forme de discours, Sanders tombe dans le travers qu’il dénonce et que sa critique perd ainsi tout son sens.